A DISASTER EMERGENCY RESPONSE CENTER BASED ON SMART CITY CONCEPT - MONELLIA (NIM : 23214086), IRA
Along with the development in technology and city governance, changes occur in terms of management of a city. Paradigm that a city should be able to ensure the sustainability of the city by optimizing resources and utilizing Information and Communication Technology (ICT) into a concept that is guided by the city administration. The concept known as "Smart City" is evolving in various aspects of urban life, including transportation, buildings, government, health, education, and others. Smart City sees a city is interconnected among its resources so that they affect each other. A disorder affecting one of its resources will immediately affect other resources. Natural and non-natural disasters add to the list of problems in a city. These disturbances result in economic losses and loss of lives thus degrading the quality of life and sustainability of a city. Disasters occurring in different parts of the world have raised awareness of the importance of disaster management in critical times, or the emergency response period. The disaster emergency response phase, which is the phase of disaster beginning until the crisis ends and the start of the disaster recovery phase, is the phase that determines the impact of a disaster. If the critical phase can be handled properly, it can minimize casualties as well as material losses due to the disaster. One form of disaster management during the emergency response period is to establish a Disaster Emergency Response Center (DERC) which is an information management center and disaster response emergency coordination center. One of the problems faced by a DERC is how to provide appropriate data and information for disaster emergency response needs and to present it in a timely manner so that decision makers can determine the optimal steps in emergency response. DERC which is the center of information and coordination in the context of emergency disaster response is essentially an office, that is where the implementation of various kinds of operational activities and organizational management in order to achieve the organization's goal of providing services for disaster emergency response. The development of information technology today provides a variety of media alternatives and devices that can be used to make inter-personal communication and access to media or information sources. This condition needs to be anticipated by DERC to provide optimal services in terms of communication and information provision so that all stakeholders can be served at any time by using various tools or media available. It takes an extension of concept in terms of providing office functions to meet this need. Ideally a DERC needs a digital office for all the needs of emergency disaster response office management. This research attempts to answer the problem of Designing DERC based on smart city concept that can provide the right data and information for emergency response needs so that decision makers can determine the most optimal steps in disaster response in the form of digital office. The analysis begins by formulate a proposed DERC concept that will be the basis for further analysis and design. The concept of DERC made is the incorporation of the concept of DERC and the concept of Smart City. Based on the concept of DERC Smart City further analysis of the preparation of emergency response indicators Smart City disaster. Furthermore, the design of DERC smart city in the form of digital office. Testing of concepts and design is done by Expert Judgment consisting of disaster practitioners, academics, researchers and city government practitioners who have implemented Smart City. The test results show the proposed concept and design has been in accordance with the concept of Smart City and can be implemented for the development of DERC management in a city. This research is expected to be a guide for disaster practitioners, city government practitioners, and academics in developing DERC in accordance with the concept of smart city in the form of a digital office that is a DERC that can provide data and information appropriate for emergency disaster response needs and coordination center for the decision makers to determine optimal measures in disaster response, so as to improve services for the community and support sustainable development.